Preclinical safety and efﬁcacy evaluation of the intrathecal transplantation of GMP-grade human umbilical cord mesenchymal stem cells for ischemic stroke - Zejia Huang; Jiaohua Jiang; Qingxia Peng; Mengzhi Jin; Yakun Dong; Xuejia Li; Ermei Luo; Haijia Chen; Yidong Wang (Neural Regeneration Research)
Intrathecal administration of human umbilical cord mesenchymal stem cells may be a promising approach for the treatment of stroke, but its safety, effectiveness, and mechanism remain to be elucidated. In this study, good manufacturing practice–grade human umbilical cord mesenchymal stem cells (5 × 105 and 1 × 106 cells) and saline were administered by cerebellomedullary cistern injection 72 hours after stroke induced by middle cerebral artery occlusion in rats. The results showed (1) no significant difference in mortality or general conditions among the three groups. There was no abnormal differentiation or tumor formation in various organs of rats in any group. (2) Compared with saline-treated animals, those treated with human umbilical cord mesenchymal stem cells showed significant functional recovery and reduced infarct volume, with no significant differences between different human umbilical cord mesenchymal stem cell doses. (3) Human umbilical cord mesenchymal stem cells were found in the ischemic brain after 14 and 28 days of follow-up, and the number of positive cells significantly decreased over time. (4) Neuronal nuclei expression in the human umbilical cord mesenchymal stem cell group was greater than that in the saline group, while glial fibrillary acidic protein and ionized calcium binding adaptor molecule 1 expression levels decreased. (5) Human umbilical cord mesenchymal stem cell treatment increased the number of CD31+ microvessels and doublecortin-positive cells after ischemic stroke. Human umbilical cord mesenchymal stem cells also upregulated the expression of CD31+/Ki67+. (6) At 14 days after intrathecal administration, brain-derived neurotrophic factor expression in the peri-infarct area and the concentrations of brain-derived neurotrophic factor in the cerebrospinal fluid in both human umbilical cord mesenchymal stem cell groups were significantly greater than those in the saline group and persisted until the 28th day. Taken together, these results indicate that the intrathecal administration of human umbilical cord mesenchymal stem cells via cerebellomedullary cistern injection is safe and effective for the treatment of ischemic stroke in rats. The mechanisms may include alleviating the local inflammatory response in the peri-infarct region, promoting neurogenesis and angiogenesis, and enhancing the production of neurotrophic factors.